Governing groundwater with knowledge, motivation, and agency - Sanil, Richu; Zwarteveen, Margreet; Bruns, Bryan; Meinzen-Dick, Ruth S. (CGIAR, 2024)
Groundwater is an increasingly vital common pool resource for water supply, irrigation, and ecosystems, but difficult to govern. While there are many institutional tools for governing groundwater, there are no panaceas, and successes are rare. Effective groundwater governance requires that key stakeholders have combinations of knowledge, motivation, and agency to act together effectively. This webinar shares results from research on groundwater governance, including findings from a special issue of the International Journal of the Commons.